A Difficult Case to Diagnose: Machado-Joseph Disease/Spinocerebellar Ataxia Type III - Muhammad Sohail Ajmal Ghoauri; Nauman Ismat Butt; Dur-; Muhammad Bilal Rasheed; Muhammad Umair Javed; Fahmina Ashfaq (Aziz Fatimah Medical and Dental College, 2023)
Machado-Joseph Disease, also known as Spinocerebellar Ataxia Type III, was initially described in patients of Azorean heritage as a neurodegenerative disease but is now known to occur globally. The main clinical involvement is cerebellar and brainstem dysfunction causing progressive ataxia and usually disease onset is in young-adult to mid-adult years. A 20-year old female presented with a 3-year history of gradual onset, progressively worsening gait abnormality and tremor of the right hand. On examination, she had gargoyle-like facial features and pes cavus. On neurologic examination, she had dystonic tremor of right hand, cerebellar ataxia, dysdiadokokinesia, abnormal heel-shin coordination, hyperreflexia with downgoing plantar reflex bilaterally. Her MRI scan brain revealed communicating hydrocephalus with cerebellar atrophy. She was diagnosed with Machado-Joseph Disease/Spinocerebellar Ataxia type III.